The Determinants of Bank Capital for East Asian Countries - Ahmad, Rubi; Albaity, Mohamed (SAGE Publications, 2019)
This study identifies the determinants of bank capital ratios in eight East Asian countries using unbalanced panel data of 278 banks from 2004 to 2014. The results indicate that bank capital decisions are significantly driven by management quality, liquidity, leverage and bank size, as well as bank regulations, indicating that the determinants of bank capital are consistent with past findings for US and European banks. The capital adequacy ratios in East Asia are not linked with banks’ risk appetite. Given that our results show that bank managers generally react negatively to capital requirements, capital regulations should be followed with more rigorous supervisory oversight, to reduce the adverse effects of high capital requirements on bank safety. © 2019 International Management Institute, New Delhi.